Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1021/ma991196u
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic Simulations of Glassy Polystyrenes with Realistic Chain Conformations

Abstract: The detailed structure of glassy polymers is still a subject of debate. One of the main accepted views is Flory's hypothesis, 1-3 according to which the chain conformation in the glassy state is close to that in the melt or in solutions under θ conditions. However, other structural models with higher degrees of local order have been put forward (see Sperling 4 for a collection of references). Until recently, the structure of glassy polymers has mainly been studied by scattering techniques; in most studies, exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 16 publications
1
17
0
1
Order By: Relevance
“…NMR measurements on atactic PS have helped gain insight into the conformations adopted by its chains. Suter and collaborators [51][52][53][54] The fusion of trans and gauche states is apparently produced by the atomistic potential at this high temperature, since it is also present in the single-chain system which has been equilibrated by MD. Comparing the curves in Figures Figure 5 and Figure 6 we observe that torsion angle distributions in the reverse-mapped structures are extremely close to those obtained from the 80mer structure that was directly equilibrated by MD at the atomistic level, without intervention of any coarse-graining and reverse mapping.…”
Section: Thermodynamic Properties and Structure Of The Reverse-mappedmentioning
confidence: 99%
“…NMR measurements on atactic PS have helped gain insight into the conformations adopted by its chains. Suter and collaborators [51][52][53][54] The fusion of trans and gauche states is apparently produced by the atomistic potential at this high temperature, since it is also present in the single-chain system which has been equilibrated by MD. Comparing the curves in Figures Figure 5 and Figure 6 we observe that torsion angle distributions in the reverse-mapped structures are extremely close to those obtained from the 80mer structure that was directly equilibrated by MD at the atomistic level, without intervention of any coarse-graining and reverse mapping.…”
Section: Thermodynamic Properties and Structure Of The Reverse-mappedmentioning
confidence: 99%
“…Then, these samples would exhibit isotropic magnetic susceptibility and, at first, would show no preferential orientation when immersed in a magnetic field. In this regard, experimental and theoretical studies on a ‐PS in bulk have provided evidence of only short range order (∼6 Å) 28–31. However, studies in a ‐PS very thin films (i.e., thickness less than 500 nm) have shown that the phenyl groups at an interface air‐polymer tend to be oriented with the carbon in p‐position pointing away from the surface and the plane defined by the ring parallel to the surface normal,32–34 whereas at a solid–polymer interface the ring planes are oriented perpendicular to the surface normal 32.…”
Section: Resultsmentioning
confidence: 99%
“…Spyriouni et al were successful in preparing PS in the melt with correct global chain conformations; on the more local level, discrepancies were observed between their distributions of dyad conformations and those suggested by NMR data of Robyr et al [14][15][16] . This justifies renewed attempts, such as ours, to prepare well-equilibrated PS.…”
Section: Full Papermentioning
confidence: 99%
“…This justifies renewed attempts, such as ours, to prepare well‐equilibrated PS. Comparison to the NMR data of Robyr et al14–16 is performed in the separate publication 12. In general, our algorithm, which is applicable to other polymers than PS as well, is very useful when more detail than provided by 1:1 models is required.…”
Section: Introductionmentioning
confidence: 99%